2021
DOI: 10.1186/s12911-021-01651-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of quality of routine health information system data and associated factors among departments in public health facilities of Harari region, Ethiopia

Abstract: Background Despite the improvements in the knowledge and understanding of the role of health information in the global health system, the quality of data generated by a routine health information system is still very poor in low and middle-income countries. There is a paucity of studies as to what determines data quality in health facilities in the study area. Therefore, this study was aimed to assess the quality of routine health information system data and associated factors in public health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 21 publications
1
13
1
Order By: Relevance
“…Data quality was measured as the fitness of data use based on three dimensions: accuracy ≥80%, completeness ≥85%, and timeliness ≥85%. 26 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data quality was measured as the fitness of data use based on three dimensions: accuracy ≥80%, completeness ≥85%, and timeliness ≥85%. 26 …”
Section: Methodsmentioning
confidence: 99%
“…Data quality was measured as the fitness of data use based on three dimensions: accuracy ≥80%, completeness ≥85%, and timeliness ≥85%. 26 Availability of adequate amount of DHIS2 format. It refers to the presence of the following formats for at least the previous 3 months to the next 2 months: tally sheets, registers, and report forms.…”
Section: Operational Definitionsmentioning
confidence: 99%
“…These findings are echoed by a case series in the literature comparing data on four common under-five children’s illnesses in outpatient registers and monthly reports in Tanzania that found low completeness and timeliness of reporting and over-reporting of diagnoses [ 82 ]. Similarly, an HMIS review in Ethiopia using PRISM tools found lower register completeness compared to facility report completeness, and low data accuracy comparing reports to registers [ 83 ]. One systematic review focused specifically on childhood vaccination data quality in LMIC, comparing health facility data with patient recall, home-based records, and serology, as well as different combinations of data sources with one another, finding that facility data generally had better agreement with serology than surveys or home-based records [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Improved capacity of systematic and quality surveillance and data recording in health system is needed. There are also gaps in the quality of routine health information system data in public health facilities at regional level compared to national level ( 40 ). Lack of trained personnel compromise quality of surveillance and data reporting.…”
Section: Section 4: Discussion On Challenges and Way Forwardmentioning
confidence: 99%
“…Lack of trained personnel compromise quality of surveillance and data reporting. Regular training programs for health workers at regional, woreda, and kebele levels with committed supervision and feedback are essential ( 40 ). To enhance surveillance and laboratory capacity at all levels for early detection and case confirmation by 2028 and reducing cholera-associated mortality by 100% in cholera hotspot woredas by 2028 with no local transmission ( 18 ), sufficient structured capacity building program for health system strengthening is warranted.…”
Section: Section 4: Discussion On Challenges and Way Forwardmentioning
confidence: 99%